Industrial training report: System and New Media Department, The Office of Library and Knowledge Management, Universiti Malaysia Kelantan / Nik Amierah Noornadrah Ma'roof - Ma'roof, Nik Amierah Noornadrah (Perpustakaan Tengku Anis, 2015)
The academic writing report paper is based on the period from 1 February 2014 to 30 June 2014 in System and New Media Department at The Office of Library and Knowledge Management, Universiti Malaysia Kelantan. During the practical training period, the trainee had been exposed with a various new stuffs that never been taught during the studies. In fulfil the core requirement as a Bachelor of Information Science (Hons.) Information System Management student, the trainee was given the task to get involved in several systems development projects includes Online Bibliography of Entrepreneurship Website, UMK Press Online Book Store System, Autonomy Audit Repository System, Digital Kelantan Collection and UMK Library HelpDesk Support Ticket System. However, most of the development process in developing those systems was no required the trainee to come out with coding instead of installing the open source platform such as Drupal, Omeka, OpenCart and osTicket. Therefore, that has result the trainee in skipping a few steps of System Development Life Cycle. Sometimes, the trainee feels like the responsibility towards the system developments is as a database administrator not a developer. Besides all of the system development tasks, the trainee also required to organize a few events and outreach programs includes to conduct user education and training. Besides that, the trainee was also helping the organization in doing the library tasks and records management work. Surprisingly, the trainee feels that all of those works done was related with the course work that has been learnt during the studies in Faculty of Information Management, UiTM.